SpoIVA is an essential morphogenetic protein for the formation of heat- and lysozyme-resistant spores in Clostridium sporogenes NBRC 14293 - Kuwana, Ritsuko; Dupuy, Bruno; Martin-Verstraete, Isabelle; Takamatsu, Hiromu (Frontiers in Microbiology, 2024)
Clostridium sporogenes is an anaerobic spore-forming bacterium genetically related to Clostridium botulinum but lacks toxin genes. The sporulation mechanism and spore structures of anaerobic bacteria, including C. sporogenes, have not been comprehensively analyzed. Based on 16S rRNA gene analysis, it has been determined that C. sporogenes NBRC 14293 belongs to C. botulinum Group I. Moreover, SpoIVA is highly conserved in Bacillus and Clostridium species. Therefore, the aim of the present study is to investigate the mechanism of spore formation in C. sporogenes by performing a functional analysis of spoIVA encoding SpoIVA, a protein involved in the early development of the spore coat and cortex in Bacillus subtilis. Inactivation of spoIVA in C. sporogenes resulted in the loss of resistance of sporulating cells to lysozyme and heat treatments. Phase-contrast microscopy indicated that the inactivation of spoIVA caused the development of abnormal forespores and production of only a few immature spores. In the spoIVA mutant, abnormal swirl structures were detected in the mother cell using both phase-contrast and transmission electron microscopy. These swirls were stained with auramine O, pararosaniline hydrochloride, and 2-(4-aminophenyl) benzothiazole to examine the surface of mature spores of the wild-type strain. We found that the spore coat and exosporium proteins were misassembled and that they accumulated in the mother cells of the mutant. The results of this study indicate that SpoIVA is a spore morphogenetic protein, providing novel insights into spore morphogenesis in C. sporogenes.